Identity Politics, Citizenship and the Soft State in Indonesia: An Essay - Henk Schulte Nordholt (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2008)
Since 1998, administrative decentralisation, regional autonomy and ethnic and religious conflicts in areas outside Java have put identity politics high on the political agenda in Indonesia. This paper examines various expressions of these new identity politics and how they are related to, and derived from, older colonial concepts and categories. Examples from Riau and Bali illustrate how ethnic and religious repertoires are used to express political ambitions and mobilise popular support. Since 1998 Indonesia also witnessed a successful transition to electoral democracy. Whether democracy will take root in a more substantial way depends on the extent to which a notion of citizenship can be reinforced. It is argued that this notion of citizenship can only be maintained through the strengthening of the rule of law. In this respect it is also important to focus on the uneasy relationship between electoral democracy and ethnic and religious sentiments that tend to give far more attention to exclusive group interests while excluding a shared sense of citizenship. The paper concludes that democracy and citizenship, which are based on the rule of law, can only be achieved by strengthening the administrative and law-enforcing capacity of the state.